2006
DOI: 10.1007/s00248-005-0121-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation and Leaching of Biological Soil Crust Communities in Mesic Temperate Soils

Abstract: Biological soil crust is composed of lichens, cyanobacteria, green algae, mosses, and fungi. Although crusts are a dominant source of nitrogen (N) in arid ecosystems, this study is among the first to demonstrate their contribution to N availability in xeric temperate habitats. The study site is located in Lucas County of Northwest Ohio. Using an acetylene reduction technique, we demonstrated potential N fixation for these crusts covering sandy, acidic, low N soil. Similar fixation rates were observed for crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 29 publications
1
60
2
1
Order By: Relevance
“…As the primary source of N input in many arid and semi-arid ecosystems, BSCs make an important contribution to the ecosystem N budget. BSCs play an essential role in soil stability and nutrient cycling and contribute significantly to soil fertility (Eldridge, 1998;Issa et al, 2001;Issa et al, 2007;Hu et al, 2003;Veluci et al, 2006). Soil surface structure is altered by BSCs through the creation of a rough surface micro topography, which alters the movement and retention of nutrients by diminishing the impact of surface runoff and wind (Veluci et al, 2006;Housman et al, 2007).…”
Section: Biological Soil Crustsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the primary source of N input in many arid and semi-arid ecosystems, BSCs make an important contribution to the ecosystem N budget. BSCs play an essential role in soil stability and nutrient cycling and contribute significantly to soil fertility (Eldridge, 1998;Issa et al, 2001;Issa et al, 2007;Hu et al, 2003;Veluci et al, 2006). Soil surface structure is altered by BSCs through the creation of a rough surface micro topography, which alters the movement and retention of nutrients by diminishing the impact of surface runoff and wind (Veluci et al, 2006;Housman et al, 2007).…”
Section: Biological Soil Crustsmentioning
confidence: 99%
“…BSCs play an essential role in soil stability and nutrient cycling and contribute significantly to soil fertility (Eldridge, 1998;Issa et al, 2001;Issa et al, 2007;Hu et al, 2003;Veluci et al, 2006). Soil surface structure is altered by BSCs through the creation of a rough surface micro topography, which alters the movement and retention of nutrients by diminishing the impact of surface runoff and wind (Veluci et al, 2006;Housman et al, 2007). Several studies have found BSCs to have natural abundance 15 N values indicative of fixation of atmospheric sources, higher total and mineralizable N and higher dissolved nitrogenous compounds in porewater compared with adjacent soils (Evans & Ehleringer, 1993;Belnap, 1996;Evans & Belnap, 1999;Smith et al, 2002;Johnson et al, 2005;Marsh et al, 2006).…”
Section: Biological Soil Crustsmentioning
confidence: 99%
See 2 more Smart Citations
“…They can have important impacts on ecological function through physiological or physical processes. For example, BSCs can bind soil particles to protect the surface soil from wind and water erosion (Belnap and Gardner 1993;Eldridge and Leys 2002;Veluci et al 2006;Mazor et al 1996); fix nitrogen (N) and carbon (C) to increase soil nutrients and C storage (Austin et al 2004;Hawkes 2003;Evans and Ehleringer 1993;Lange et al 1994); modify the balance between water run-off and infiltration (Kidron and Yair 1997;Eldridge and Greene 1994); and influence soil roughness. These changes can create a suitable primitive habitat for vascular plant growth, which influence on seed germination and establishment.…”
Section: Introductionmentioning
confidence: 99%